1997
DOI: 10.1002/(sici)1096-9861(19970120)377:3<324::aid-cne2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Organ cultures of embryonic rat tongue support tongue and gustatory papilla morphogenesis in vitro without intact sensory ganglia

Abstract: Taste buds on the mammalian tongue are confined to the epithelium of three types of gustatory papillae: the fungiform, circumvallate, and foliate. The gustatory papillae are composed of an epithelium that covers a broad connective tissue core, with extensive innervation to taste bud and nongustatory epithelial locations. Although the temporal sequence of gustatory papilla development is known for several species, factors that regulate initiation, growth, and maintenance of the papillae are not understood. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…To more closely examine the interactions of Wnt and Shh signaling molecules during taste papilla development, we turned to organ culture of embryonic tongues. Rodent tongues in culture have been shown to closely mimic in vivo spatial and temporal stages of morphogenesis and molecular expression, and to support the development of taste papillae (22,23). Because the expression of Shh and Wnt signaling components in mice is seen only after E12.5, we maintained stage E12.5 (or E11.5; data not shown) tongues in culture for up to 2 days under varying treatment conditions.…”
Section: Shh Expression In Fungiform Papillae Is Reduced By the Absenmentioning
confidence: 99%
“…To more closely examine the interactions of Wnt and Shh signaling molecules during taste papilla development, we turned to organ culture of embryonic tongues. Rodent tongues in culture have been shown to closely mimic in vivo spatial and temporal stages of morphogenesis and molecular expression, and to support the development of taste papillae (22,23). Because the expression of Shh and Wnt signaling components in mice is seen only after E12.5, we maintained stage E12.5 (or E11.5; data not shown) tongues in culture for up to 2 days under varying treatment conditions.…”
Section: Shh Expression In Fungiform Papillae Is Reduced By the Absenmentioning
confidence: 99%
“…Similarly, Ptc, Gli1, Bmp-2 and Bmp-4 are expressed in the dorsal epithelium and share similar punctate patterns at regular intervals which are often symmetrically located in rows at both sides of the median sulcus. At E 14, small eminencies on the anterior part of the tongue are distinguished as the first morphological indications of fungiform papillae through a dissecting microscope [45]. Shh transcripts continue to be expressed in the developing fungiform papillae in discrete spot patterns at E 14-15.…”
Section: Tongue Papillamentioning
confidence: 99%
“…In vitro studies have also shown that taste buds cannot develop without innervation [20]. Although the different types of papillae can develop in the tongue of the rat when cultured in vitro in the absence of innervation, the development of functional taste buds is compromised [20,28]. Taken together these in vivo and in vitro data suggest that innervation is essential for the development of taste buds.…”
Section: Innervation and Taste Budsmentioning
confidence: 97%